Continuous-variable geometric phase and its manipulation for quantum computation in a superconducting circuit. Issue 1 (December 2017) - Song, Chao; Zheng, Shi-Biao; Zhang, Pengfei; Xu, Kai; Zhang, Libo; Guo, Qiujiang; Liu, Wuxin; Xu, Da; Deng, Hui; Huang, Keqiang; Zheng, Dongning; Zhu, Xiaobo; et al.
Abstract Geometric phase, associated with holonomy transformation in quantum state space, is an important quantum-mechanical effect. Besides fundamental interest, this effect has practical applications, among which geometric quantum computation is a paradigm, where quantum logic operations are realized through geometric phase manipulation that has some intrinsic noise-resilient advantages and may enable simplified implementation of multi-qubit gates compared to the dynamical approach. Here we report observation of a continuous-variable geometric phase and demonstrate a quantum gate protocol based on this phase in a superconducting circuit, where five qubits are controllably coupled to a resonator. Our geometric approach allows for one-step implementation ofn -qubit controlled-phase gates, which represents a remarkable advantage compared to gate decomposition methods, where the number of required steps dramatically increases withn . Following this approach, we realize these gates withn up to 4, verifying the high efficiency of this geometric manipulation for quantum computation. Geometric phase is of fundamental interest and has practical application in quantum computation. Here the authors observe continuous-variable geometric phase in a superconducting circuit and demonstrate a multi-qubit controlled phase gate protocol based on this geometric effect.